2021
DOI: 10.7717/peerj.11540
|View full text |Cite
|
Sign up to set email alerts
|

Bracon wasps for ecological pest control–a laboratory experiment

Abstract: Biological control of pest insects by natural enemies may be an effective, cheap and environmentally friendly alternative to synthetic pesticides. The cosmopolitan parasitoid wasp species Bracon brevicornis Wesmael and B. hebetor Say (Hymenoptera: Braconidae) use lepidopteran species as hosts, including insect pests like Ephestia kuehniella or Ostrinia nubilalis. Here, we compare the reproductive success of both Bracon species on E. kuehniella in a laboratory experiment. We asked (1) how the reproductive succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, Hasan et al (2019) evaluated possible improvements to the mass rearing of the larval parasitoid Habrobracon hebetor on irradiated G. mellonella and Plodia interpunctella at the dose of 150Gy proved useful for enhancing parasitism and adult emergence of H. hebetor, with significantly higher parasitism recorded at 150 and Female parasitoids favored irradiated larvae and parasitized a substantially higher number of larvae than nonirradiated larvae. Lettmann et al (2021) found that using a total number of ten host larvae to enhance the overall number of progeny and one female wasp is recommended to keep the number of hatched parasitoids per host at a high level to obtain a high level of pest management efficiency; practitioners can utilize either B. brevicornis or B. hebetor at low and high temperatures, as well as with varied host densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Hasan et al (2019) evaluated possible improvements to the mass rearing of the larval parasitoid Habrobracon hebetor on irradiated G. mellonella and Plodia interpunctella at the dose of 150Gy proved useful for enhancing parasitism and adult emergence of H. hebetor, with significantly higher parasitism recorded at 150 and Female parasitoids favored irradiated larvae and parasitized a substantially higher number of larvae than nonirradiated larvae. Lettmann et al (2021) found that using a total number of ten host larvae to enhance the overall number of progeny and one female wasp is recommended to keep the number of hatched parasitoids per host at a high level to obtain a high level of pest management efficiency; practitioners can utilize either B. brevicornis or B. hebetor at low and high temperatures, as well as with varied host densities.…”
Section: Discussionmentioning
confidence: 99%
“…The ecto-parasitoid Braconidae wasps is one of the parasitoid families' most diverse with numerous parasites (LaSalle & Gauld 1993). Bracon brevicornis Wesmael (Hymenoptera: Braconidae) is a gregarious insect that attacks many pests of Lepidoptera species as a larval ectoparasitoid (Brower et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Parasitoid nutrition is important in evaluating its reproductive performance and life span. Several studies mentioned that diluted honey [10] or sugary water [12] in general, without specifying certain concentrations, could be used when rearing B. brevicornis on S. frugiperda or E. kuehniella. However, Wei et al reported that honey-feeding and host hemolymph-feeding parasitoid shows similar effect on reproduction and longevity [13].…”
Section: Introductionmentioning
confidence: 99%